THE EFFECTIVENESS OF ANTIBIOTIC DROPS IN THE HEALING PROCESS OF INCISION WOUNDS IN WISTAR RATS MACROSCOPICALLY - Widagdo, Hagai Deosiddhanta; Jayawardhita, Anak Agung Gde; Gorda, I Wayan (Buletin Veteriner Udayana, 2023)
A wound is a break in tissue continuity due to tissue substance that is damaged or lost due to injury or surgery. Wound healing is a process of repairing skin tissue or other tissues after an injury. This study aims to determine the effectiveness of giving antibiotic drops in the healing process of incision wounds in Wistar rats (Rattus norvegicus). This study used experimental animals in the form of female wistar rats weighing 150-200 grams each, 120 days old, totaling 24 rats, which were divided into 4 groups with different treatments. The research object was adapted and then an incision wound 1.5 cm long with a depth of 0.5 mm was made on the back, then each group was given treatment, which was given drops of NaCl (T0), given drops of oxytetracycline (T1) antibiotics, given drops of amoxicillin (T2) antibiotics. , and given cefotaxime (T3) antibiotic drops. Based on the analysis of incision wound healing data in Wistar rats as seen from the signs of inflammation it had a significance value of 0.555 (P>0.05) and scabs with a significant value of 0.260 (P>0.05) which showed no significant/significant difference from the four treatment performed. Based on these results it can be concluded that the antibiotic drops given showed no different wound healing results between the four treatments.